Por que os blocos de pífano fazem tanto sucesso, afinal? - Raposo, Gabriel de Matos Brandão (2023)
Blocos de pífanos are urban communities where the fife and other elements of traditional fife band performance are practiced, also known as cabaçais bands or just cabaçais in the interior of Brazil. Since 2004, starting with Ventoinha de Canudo in Brasilia, many other groups have formed as a social phenomenon, bringing together hundreds of people in their first meetings. In at least six capitals and some other cities in the interior there are fife blocks. In some of these blocks, rehearsals focus on preparing to parade during Carnival, in others, rehearsals and presentations take place throughout the year. In this research, I show the reasons that make up the subjectivities of this social phenomenon that intensified during and in the postpandemic. This is a digital ethnography carried out by me together with the Bloco de Pífanos in São Paulo and Pifarada Urbana, in Fortaleza-Ce. I show how these blocks have formed large social networks of mutual support with fife bands from the interior, giving them a very opportune visibility when they showed signs of decline in their performance and renewal. The research was carried out during the process of recognition of fife bands as intangible cultural heritage in the state of Pernambuco in 2022, an important step towards its recognition at the national level. The title was granted on the same day of the death of the greatest representative of the fife in Brazil, Mr. Sebastião Biano da Banda de Pífanos de Caruarú, aged 103.